2021
DOI: 10.1371/journal.pone.0258844
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and factors associated with modern contraceptive use among women of reproductive age in Nigeria: A multilevel analysis

Abstract: Background Evidence suggests that in countries with high fertility and fecundity rates, such as Nigeria, the promotion of modern contraceptive use prevents approximately 32% and 10% of maternal and child mortality, respectively. Therefore, this study aimed to assess the spatial distribution of modern contraceptive use and its predictors among women of reproductive age in Nigeria. Methods The study employed a cross-sectional analysis of population-based data involving 24,281 women of reproductive age in Niger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 27 publications
17
29
0
Order By: Relevance
“…A possible reason for this finding could be that adolescents who are with the Igbo ethnic group have multiple sexual partners, increasing their likelihood of getting pregnant [ 38 ]. Another possible reason for this finding could be the low access and utilization of contraceptives among adolescents with the Igbo ethnic group, increasing their likelihood of getting pregnant [ 46 , 47 ]. Oluwasanu [ 35 ] specifically found that only 8.7, 7.8 and 5.8% of women used condoms, intrauterine devices (IUDs) and pills, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason for this finding could be that adolescents who are with the Igbo ethnic group have multiple sexual partners, increasing their likelihood of getting pregnant [ 38 ]. Another possible reason for this finding could be the low access and utilization of contraceptives among adolescents with the Igbo ethnic group, increasing their likelihood of getting pregnant [ 46 , 47 ]. Oluwasanu [ 35 ] specifically found that only 8.7, 7.8 and 5.8% of women used condoms, intrauterine devices (IUDs) and pills, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in sub-Saharan Africa showed that different sociodemographic factors, such as age, educational status, wealth index, geographical location (urban-rural), husband’s occupation, marital status, and wealth status, are associated with ANC utilization [ 16 , 17 , 18 ]. For instance, recent studies in Ethiopia (e.g., [ 2 ]), Nigeria (e.g., [ 19 , 20 ]), and other parts of sub-Saharan Africa [ 21 ] suggested that the likelihood of not receiving ANC was high among poor women, due to inadequate financing, the non-availability of competent and skilled health care providers in rural areas, distance to ANC facilities, and inadequate or poor-quality health services.…”
Section: Introductionmentioning
confidence: 99%
“…While evidence from descriptive studies suggests geographic variation in the demand for family planning to limit childbearing and the demand satisfied with modern methods in SSA [ 11 , 12 ], to our knowledge, no prior studies have quantified these spatial relationships. Despite the growing literature on spatial dimensions of contraceptive use in SSA, available studies have focused on contraceptive prevalence of modern methods among women of reproductive age [ 13 21 ] or unmet needs [ 22 , 23 ], with a majority in select countries.…”
Section: Introductionmentioning
confidence: 99%